Karakteristik Konsumen Bahan Pangan Beras Pasar Tradisional Ujung Berung - Nurfadhila, Tsalsa; Syamsiyah, Nur (Universitas Galuh, 2024)
Traditional markets are experiencing a threat to their existence in the eyes of consumers due to changes in lifestyle and the large role of access to information in changing people's behavior. Changes in prices, consumer habits and quality standards are the causes of changes in people's habits from shopping at traditional markets to other places. Ujung Berung District has 1 market that needs attention in terms of infrastructure, namely Ujung Berung Market. The problem of inadequate infrastructure and environmental conditions puts Ujung Berung Market in a worrying position in terms of competition. This research was conducted by the author to understand the characteristics of respondents and examine the characteristics of consumers of rice food so that Ujung Berung Market and its traders can know how to develop the right strategy to survive. The method used in this research is a quantitative method with descriptive analysis. The result is that Ujung Berung Market consumers are dominated by women, with an age distribution of 17 – 25 years, with the majority of income <Rp. 1,500,000 and >Rp. 3,500,001, the majority live 1 - 5 kilometers from the Traditional Market, and the majority have a history of Modern Market. <5 kilometers near his house.